Effect of cold ambient temperature on heat flux, skin temperature, and thermal sensation at different body parts in elite biathletes - Blokker, T.; Bucher, E.; Steiner, T.; Wehrlin, J. P. (Frontiers in Sports and Active Living, 2022)
Introduction: When exercising in the cold, optimizing thermoregulation is essential to maintain performance. However, no study has investigated thermal parameters with wearable-based measurements in a field setting among elite Nordic skiers. Therefore, this study aimed to assess the thermal response and sensation measured at different body parts during exercise in a cold environment in biathletes.